Hubungan Antara Dukungan Sosial Keluarga Dengan Kecemasan Bertanding Pada Atlet Voli di Kabupaten Bekasi - Saputra, Farhan; Muzammil, Ferdy; Febrieta, Ditta (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
Competitive anxiety is a negative psychological condition experienced by athletes when facing competitive situations, characterized by feelings of worry, nervousness, and uneasiness. One of the factors that influences this anxiety is family social support. Support from the family, including emotional, instrumental, informational, and companionship support, is believed to help calm athletes and enhance their self confidence during competitions. This study aims to examine the relationship between family social support and competitive anxiety among volleyball athletes in Bekasi Regency. The research used a quantitative correlational method. The sample consisted of 100 volleyball athletes aged 12 to 17 years, selected using a nonprobability sampling technique with an incidental sampling method. The data were analyzed using the Pearson Product Moment correlation test with the assistance of JASP software version 0.18.3.0. The results showed a significant negative relationship between family social support and competitive anxiety among volleyball athletes with a correlation coefficient of r equals minus 0.734 and a significance level of p less than 0.001. This indicates that the higher the social support received from the family, the lower the level of competitive anxiety experienced by the athlete. Therefore, the alternative hypothesis is accepted. This study emphasizes the important role of the family in supporting the mental well being and performance of athletes. Future researchers are encouraged to further explore other psychological factors that may influence competitive anxiety.